Overcoming barriers in the implementation of stroke care rehabilitation in a public hospital in Costa Rica - Coto-Solano, Beatriz (Frontiers in Stroke, 2024)
Stroke is a major public health concern in developing countries, where the burden of the disease is high and resources for care are often limited. While progress has been made in improving stroke care, many barriers still exist in providing adequate rehabilitation care for stroke survivors. In this paper we study the case of Costa Rica and how stroke care has been addressed in recent years.It is important to consider the particularities of Costa Rica when working on stroke rehabilitation.The existence of a socialized healthcare system, along with the consolidation of acute stroke management protocols, allows for the adequate management of the early stages. In addition to this, families play a key role in rehabilitation, particularly for a country where there is a lack of medium stay and long-stay rehabilitation centers. Therefore, providing training and education for families is essential in stroke case management.Looking towards the future, there is still a pending need to generate homogeneous stroke rehabilitation protocols throughout the national healthcare system, to ensure equitable access to health care, and to consolidate multidisciplinary groups. At the same time, the implementation of technologies is urgent, particularly considering their potential to help reduce waiting lists. Another goal is enhancing coordination with other state entities and NGOs to advance community, labor or educational reintegration of stroke patients.